Analysis of geomagnetic induced current modelling and calculation in electrical power grid - Amran A.S.; Ab Aziz N.F.; Zawawi A.A.; Yasin Z.M.; Salim N.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric grounding; Geomagnetism; Intercalation; Earth magnetic fields; Electrical power; Geomagnetic disturbance; Geomagnetic induced currents; Geomagnetic storm; In-Degree; Nodal analysis method; Voltage collapse; Electric power transmission networks